Experience, access and utilisation of fertility care for infertile men within the biomedical sector in urban Bangladesh: protocol for a qualitative study - Papreen Nahar; Gitau Mburu; Sohana Shafique; Priya Satalkar-Götz; Foyjunnaher Sultana (BMJ Open)
Introduction One in six people of reproductive age experience infertility in their lifetime throughout the world, often with devastating consequences. Men are often invisible in infertility research and services, yet masculinity and reproductive agency intersect within social, cultural and religious contexts to shape their experiences of infertility and masculine expression. This study aims to provide insights into the lived experience of male infertility, the availability and access of infertility services for men within the biomedical sector in Bangladesh and the potential willingness of men to use home-based semen testing.Methods and analysis This qualitative study will be conducted in Dhaka and Khulna districts in Bangladesh over 18 months (late 2023–2025). A total of 35 biomedically diagnosed infertile men will be selected for interview using convenience sampling. Additionally, 25 key informants, including healthcare providers from public and private fertility clinics and health policymakers, will be interviewed. Service availability will be documented by creating a list of fertility clinics and cataloguing services offered in a selection of these clinics. Both inductive and deductive thematic analysis will be used.Ethics and dissemination The study has been reviewed and approved by the Brighton and Sussex Medical School’s Research and Governance Ethics Committee (RGEC: ER/BSMS9E3G/1), Institutional Review Board of icddr,b (International Centre for Diarrhoeal Disease Research, Bangladesh) and the WHO Ethics Review Committee (WHO ERC, AID: A66040). A comprehensive participant information sheet containing the study aims, objectives and data collection procedures will be provided to eligible participants and informed consent obtained. Two dissemination workshops will be held, one with the community at the field level and another with the key stakeholders, that is policymakers, health service and clinical stakeholders to disseminate the results of the study and its implications for fertility care for men with infertility in Bangladesh and other low- and middle-income countries. Scientific manuscripts will be published in open-access journals to inform the global community.